Fatigue behaviour of Plasma Sprayed Titania and Chromia Coatings - Koutsomichalis Angelos (EDP Sciences, 2021)
Cr2O3 and TiO2 powders were deposited by atmospheric plasma spray (APS) on steel substrates. Microstructural analysis of the coatings showed typical lamellar structure with good coating quality. Fatigue strength was studied by using cyclic testing (measuring with an inhouse-built apparatus the strength of the coated systems under a wide range of impact cycles) and static loading tests (Vickers tests standards with 600N and 1500N) measuring the adhesion properties of the coatings. In low cycles (1x103) Titania coatings exhibited better strength, while at intermediate (4.5x105) and high (1x106) number of impact cycles, both Chromia and Titania coatings exhibited quite similar strength characteristics. At low impact force the thickness of the coatings plays critical role with better performance obtained by Chromia coatings. During static loading both coatings exhibited similar characteristics at the crater diameter but with larger crater depth for Titania. Chromia coatings exhibited higher strength resistance than Titania coatings with better mechanical properties and coating structure.